Contemporary patterns of labor in nulliparous and multiparous women - Ashwal, Eran; Livne, Michal Y.; Benichou, Jennifer I.C.; Unger, Ron; Hiersch, Liran; Aviram, Amir; Mani, Ariel; Yogev, Yariv (American journal of obstetrics and gynecology, 2020)
Controversy surrounds the definition of “normal” and “abnormal” labor. In this study, we used contemporary labor charts to explore labor patterns in large obstetric population (2011–2016). Detailed information from electronic medical records of live singleton deliveries at term (≥37 weeks of gestation) was extracted. Cases of elective cesarean deliveries, nonvertex presentation, and cesarean deliveries during the first stage of labor were excluded. Overall, 35,146 deliveries were included, of whom 15,948 deliveries (45.3%) were of nulliparous women. Median cervical dilation at admission was not significantly different between nulliparous (median, 4 cm; interquartile range, 3–5 cm) and multiparous women (median, 4 cm; interquartile range, 3–6 cm). In all, 99.3% of the women delivered vaginally. For nulliparous women, the median duration of the first stage of labor was 274 minutes (interquartile range, 145–441 minutes; 95th percentile, 747.5 minutes). Likewise, for multiparous women, the corresponding duration was 133 minutes (interquartile range, 56–244 minutes; 95th percentile, 494 minutes). During the latent phase (cervical dilation at admission, ≤4 cm), the time elapsed to the second stage of labor was 120–140 minutes longer in nulliparous women, whereas the gap between the groups decreased dramatically with advanced cervical dilation on admission. Nulliparous and multiparous women appeared to progress at a similar pace during the latent phase; however, after 5 cm, labor accelerated faster in multiparous women. Epidural anesthesia lengthens duration first and second stages of labor in all parities. Partograms according to cervical dilation at presentation are proposed. Cervical dilation rate is relatively constant between nulliparous and multiparous pregnant women during the latent phase. Time interval of the first stage was far slower than previously described, which allowed labor to continue for a longer period during this stage. These findings may reduce the rate of intrapartum iatrogenic interventions.